Barrier to health protocol adherence during exercise among youth in the COVID-19 pandemic era - Fitrawan Silvano; Amila Yashifa; Daniel Simada Pandapotan Saragih; Claudia Gunawan; Aningdyanungtias Inas Wuragil; Resa Paksi Mandariska; Supriyati Supriyati (Journal of Community Empowerment for Health, 2021)
Physical inactivity is one of the non-communicable disease risk factors. This study discusses how the Coronavirus Disease-2019 (COVID-19) has increased the leisure time, including among youth. The health promotion to improve the physical activities of youth is needed. This study aimed to analyze the level of compliance among Indonesian people particularly the young adults towards health protocol during exercise and conduct an intervention accordingly. This study used an action research design, with consecutive sampling. Respondents were Indonesian young adults who exercise outside of their homes during the COVID-19 pandemic. A total of 361 Indonesian young adults aged 18-25 years old, who exercise during the pandemic inside and/or outside the home, and willing to answer the questionnaire completed the online questionnaire. The questionnaire was developed from the six health protocols’ criteria from the Ministry of Health of the Republic of Indonesia. Data analysis used chi-squared tests. Furthermore, a short video was developed according to the main research findings and published on Instagram TV as a health intervention to the respondents. The results showed that the level of compliance among Indonesian young adults toward health protocol during exercise was low (24.1%). Moreover, only 35.3% of respondents applied physical distancing and 48.7% of respondents wore masks during at low-moderate intensity exercise. There was no significant association between gender, exercise intensity, and perception of the health protocol and the compliance of health protocol during exercise. In addition, the audience response toward the video campaign about health protocol during exercise was good with more than 1,000 views, 166 likes, and 50 comments. This study concluded that health promotion media that were developed based on the needs assessment results were effective to reach the target audiences.